The Role of Budgetary Control in Enhancing Corporate Financial Accountability and Transparency - Santorry Santorry; Bagas Johantri; Muhammad Agus Muljanto (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines the role of budgetary control in enhancing corporate financial accountability and transparency within organizational governance. Research Methodology: This research uses a qualitative approach with a literature study (library research) method to analyze the data. Data were collected from peer-reviewed international journal articles published within the last ten years and analyzed using qualitative content analysis to identify the key conceptual relationships. Results: The findings show that budgetary control plays an important role in strengthening financial accountability and transparency by supporting financial planning, monitoring, and evaluation. It also enhances managerial responsibility, improves financial reporting quality, and reduces information asymmetry, offering actionable insights into organizational practices. Conclusions: The study concludes that budgetary control functions not only as a financial planning instrument but also as a strategic governance mechanism that promotes accountability and transparency in corporate financial management. Limitations: This study is limited to a literature review and does not include primary empirical data. Contributions: This research highlights the practical importance of budgetary control for managers and policymakers in strengthening governance, improving financial discipline, and supporting transparent decision-making.